Effectiveness of Mussel Shells (Polymesoda erosa) as an Adsorbent to Improve Water Quality - Sari Larosa (PRISMA FISIKA, 2022)
From a quality point of view, peat water cannot be used for clean water resources, therefore it is necessary to improve the quality of peat water. An alternative effort to treat peat water can be done by adsorption process using seashell shell adsorbents. This study aims to analyze the effectiveness of mussel shells (Polymesoda erosa) as an adsorbent to improve the quality of peat water. The size of the adsorbent particles is varied, namely 8 mesh, 50 mesh, and 200 mesh. We used 30 grams of adsorbent for 300 ml water sample. The results were that the adsorbent for clam shells was able to reduce the TDS level from 402 mg/l to 112 mg/l, increase the pH level from 3.43 to 7.6 from an acidic state to an alkaline state. In this case, peat water is then suitable for use. Based on the test results, within 12 hours of contact time there was an increase in levels for all parameters along with the increase in the size of the adsorbent particles. Whereas in the contact time of 7 days, the test results experienced a decrease in levels for all parameters along with the increase in the size of the adsorbent particles which is a good optimum contact time in the adsorption process. However, the adsorbent of seashell shell has not been used effectively to adsorb turbidity and color parameters.1